Os caminhos da política de acessibilidade da UFG como afirmação dos direitos das pessoas com deficiência - Luz, Katariny Labore Barbosa da (2018)
The research focuses on the right of access and permanence of persons with disabilities to higher education. Its objective is to analyze the process of implementation of the accessibility policy of the Federal University of Goiás and its relation with a guarantee of the right of the disabled person in education, through social administration of this public policy, in a historical cut of the year 2008 (creation of NA / UFG) until the year 2017, year of implementation of the Policy. The theoretical north of the research encompasses discussions of accessibility and inclusion without higher education, barriers to accessibility and effectiveness of the rights and dignity of the disabled person. A qualitative research, choosing as techniques of data collection, documentary analysis, from consultations, portarregas, normative and official resolutions of government and university, as well as semi-structured interviews with the main responsible for implementation of this policy, the former managers of the Regional Accessibility Center of Goiânia, headquarters of the Integrated System of Accessibility Centers - SINAce / UFG, and the current managers and managers of the Accessibility Centers of the Catalão, Goiás, Goiânia and Jataí Regions, the data analysis was facilitated by the technique of content analysis. This research evidences a promotion of the right of access of persons with disabilities to higher education, ideal for the achievement of dignity and citizenship, as well as the role and commitment of the UFG in the realization of this right.